Under the background of One Belt And One Road,Chinese Taoist traditional sports and health culture studies on international communication (The Journal of the International Society of Chinese Health Practices, 2021)
Objective: Taoist traditional sports preservation has a long history and is one of the excellent traditional culture. Mr. Lu Xun once said, "The root of China is all in Taoism. " As a local religion in China, its health culture plays an important role in improving the soft power of Chinese culture. Based on the historical characteristics and cultural attributes of the traditional Chinese Taoist sports preservation, the reality investigates the internationalization of the traditional Taoist sports preservation culture under the background of "One Belt And One Road". Taoism traditional sports health is the source of culture, the root of tradition, the soul of a form of physical expression, Taoism traditional sports health culture as a special form of sports closely combined with the great rejuvenation of the Chinese nation, so this article aims to promote the international dissemination of Taoism traditional sports health culture, improve the soft power of our traditional sports culture. Methods: To study the current situation, the dilemma and the countermeasures of the strategic background of "One Belt And One Road" of traditional sports health culture. Follow the basic idea of "—— scientific analysis —— system arrangement". First, the theme words "One Belt And One Road", "sports culture", "Taoist health preservation" and "international communication" to carry out the search and mathematics of relevant documents. Secondly, from the perspective of the international communication of Taoist traditional sports, using the analysis of interdisciplinary methods, to sort out a set of reliable and detailed theoretical basis. Finally, the logical analysis method is used to comb, summarize and summarize the status quo, dilemma and development path of traditional Chinese Taoist sports and health culture under the background of "One Belt and One Road". Results: in the process of the "difference" period, Chinese Taoist traditional sports culture embodies our ideological spiritual heritage and national value pursuit, it is rooted in the tradition, and with the development of the era and extract the new value of the era and representative ideas, both has the development of the era needs to construct demand, and in line with the reality of the development of characteristic socialism. The combination of traditional Taoist sports health combined with the international dissemination of "One Belt And One Road" is conducive to the extensive coordination and integration of traditional culture and sports culture, and helps to promote the vigorous development of Chinese traditional Taoist sports health culture in the trend of globalization. At the present stage, the "One Belt And One Road" strategic background provides a carrier for the dissemination of traditional Taoist sports health culture in China, and the traditional Taoist sports health culture provides an opportunity for international cultural exchanges. Taoism has a high voice in the cultural communication of traditional sports health. Analyze the motivation for the formation factors of the traditional Taoist sports health culture, provide a serious and grand historical vision, and improve the soft power of Chinese culture based on the modern Taoist traditional Taoist sports health culture. The international dissemination and development of Taoist traditional sports and health culture has injected it with the national cultural concept and will. The exchange of "One Belt And One Road" strategic layout and the historical encounter of the traditional Taoist sports health culture carry forward the national concept and national culture, and promote the humanistic concept and scientific spirit of China's health preservation. Conclusion: (1) Under the background of "One Belt And One Road", the dilemma of international communication of Chinese traditional Taoist sports health culture countries mainly has the following 5 points: First, self-preservation culture: "lost self" of Chinese traditional Taoist sports health culture. Second, Chinese culture misreading: the "regional difference" of the traditional Chinese Taoist sports health culture results in the lack of accurate traditional Taoist sports health awareness, and the level of cultural exchange and governance needs to be improved. Third, the transmission mode lags behind: the "carrier" of traditional Chinese Taoist sports and health culture is insufficient, and the treasures of traditional health preservation are difficult to meet the needs of health preservation of various countries. Fourth, the communication means is rigid: the "lack of symbols" of the Chinese traditional Taoist sports health preservation culture does not use the historical symbols to publicize the enthusiasm of the traditional Taoist sports health preservation culture. Fifth, the communication system needs to be constructed: the "memory shortage" of the traditional Chinese Taoist sports and health culture, the collective memory and sharing system has not been accurately established, and most countries along the Road are alert to Chinese culture. (2) "One Belt And One Road" of globalization, as an important way to participate in "One Belt And One Road" is a historical encounter of cultural integration. The dissemination of the internationalization of the traditional Taoist sports health culture needs to think about how to implement strategic coordination under the influence of various strong cultures and strong media, form strategic synergy, expand communication channels and enhance the international discourse voice. Therefore, the paper for the "area" under the background of Chinese Taoist traditional sports health culture international communication of international dilemma, is put forward: first, cultivate national traditional sports culture consciousness, construct Taoist traditional sports health culture communication content system, build Taoist traditional sports health culture in international communication card, enhance cultural affinity and cross-border national cultural identity. Second, face up to the cultural differences of "One Belt And One Road" countries, build differentiated communication models, carry forward the Chinese national culture, and enrich the spiritual and cultural life. Third, we will build three-dimensional communication means, enhance the discourse voice of China's cultural communication, and realize the vision of peace and open ideas of all countries. Fourth, improve the traditional sports and health culture skills of Chinese Taoism, and promote the dissemination of "wisdom". Fifth, excavate the traditional Chinese Taoist sports and health culture memory resources, build a cultural sharing system, and promote the exchange of Chinese culture in most countries along the Belt and Road.